IMPLEMENTASI SISTEM KONTROL PENGGERAK MOTOR STEPPER PADA PROSES MOLDING MICROPLASTIC BERBASIS PID MENGGUNAKAN PLC DAN ARDUINO - Alvian Anggiana Putra; Muhamad Rifai; Hari Kurnia Safitri (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
The current industry has entered an era where every production process incorporates automation and data exchange in its manufacturing. This era is known as Industry 4.0. Industry 4.0 has had a significant impact on various industrial sectors, particularly in the production of plastic goods using techniques such as injection molding. This process is capable of producing more precise products. In the injection molding process, a well-controlled system is needed to guide plastic pellets according to the intended mold design, utilizing actuators like stepper motors. This research aims to apply the PID (Proportional-Integral-Derivative) method to control stepper motors in microplastic molding processes. The proposed system has been successfully implemented and can produce products according to the planned specifications. The most suitable PID parameter values for controlling the stepper motor are Kp = 14, Ki = 0.007, and Kd = 7000. Changing the setpoint value from 2500 to 2700 has an impact on the molding results, with the best results achieved at a setpoint value of 2700. A setpoint value of 2700 ensures that the mold and nozzle are in the correct, tight position, allowing the molding process to proceed smoothly in line with the provided design.